Piezoelectric passive control for whirl-flutter presenting structural discontinuous effects - Suenai Haramura Bastos, Savio Mho [UNESP]; Grombone de Vasconcellos, Rui Marcos [UNESP]; AIAA (Amer Inst Aeronautics & Astronautics, 2024)
Nonlinearities, such as freeplay, are intrinsic to aeronautical structures, arising due to the material employed, joints or aging, among other sources. Commonly neglected during the modeling and analysis of distinct aeroelastic problems, such nonlinearities can generate unforeseen behaviors that can be dangerous. Considering propeller driven aircraft, whirlflutter is an instability related with aeroelastic interactions amid structural, aerodynamics and gyroscopic effects of rotors, influencing the structural stability security margins and the design of wings, pylons and engine mounts. Therefore, a realistic prediction, including non-linear structural behavior and different techniques to control this instability are necessary. The present research proposes the passive control of this instability through the application of a piezoelectric material in a unimorph harvester configuration, in the presence of discontinuous structural effects due to freeplay nonlinearity. To understand the behavior and the effectiveness of this control technique, a bifurcation analysis of a 2-DOF nonlinear system which describes the pitch and yaw motions of a rotor submitted to whirl-flutter is applied. The engine mounting is represented by a combination of a rigid shaft supported by torsional springs, allowing for angular pitch and yaw movements, with the inclusion of piezoelectric material and a concentrated piecewise representation for freeplay nonlinearity in structural rigidity. As main result, it has been observed that the presence of piezoelectric in a unimorph harvester configuration can postpone the whirl-flutter instability.